Analisis Kritis Konstruksi Pengaturan Autopsi dalam Proses Penyidikan Tindak Pidana Pembunuhan di Indonesia - Wahyu Dwi Nur Cahyo; Asyharul Muala (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2022)
Autopsy is a surgical examination of a corpse to determine the cause of death. In practice, the autopsy is often rejected by the victim's family based on religion or culture reasons. Article 222 of the Criminal Code said anyone who obstructs the autopsy is subject to criminal penalties. However, in Article 134 of the Code a quo, family rejection is implicitly permissible because in the formulation of the article there is no further information regarding family rejection. This study discusses the problems of autopsy regulations, and the urgency of autopsy implementation in Indonesia legal system. Through normative juridical methods, two research results were found: The implementation of forensic autopsies in Indonesia has a weakness because of ambiguity seen in articles 133 and 134 KUHAP which regulate notification to the victim's family to perform an autopsy. Thus, it creates legal uncertainty because there aren’t autopsy technical regulations. In addition, explanatory of victim's family regarding the results of the autopsy and the influence of law enforcement can be an obstacle due to discretion of the investigator by canceling the autopsy at the request. The urgency of an autopsy is to reveal unnatural death of a person, determine whether there was a murder or not and seek material truth, so that it can be linked to the purpose of law. Through the autopsy process, the reason for the victim's death can be explained in the visum et repertum. Then a clear conclusion is drawn about the reason for the death of the victim.